Porcine Paradox: Review of The Medieval Pig by Dolly Jørgensen (2024) - Crannell-Ash, Marissa (Humanimalia, 2024)
Review of:Dolly Jørgensen, The Medieval Pig. Nature and Environment in the Middle Ages 9. Woodbridge: Boydell Press, 2024. xii + 117 pp. 26 b/w illus. £$19.99 (paperback).